Accountability and Transparency in Public Administration for Improved Service Delivery - Birdayanthi, Birdayanthi; Yusriadi, Yusriadi; Ikmal, Ikmal (Journal Social Civilecial, 2025)
Accountability and transparency are foundational pillars of effective public administration, serving as essential components for building trust, enhancing service delivery, and fostering good governance. In recent decades, the global emphasis on improving public administration has been fueled by the increasing demands of citizens for efficient, equitable, and reliable public services. The principles of accountability and transparency have become particularly relevant in addressing governance challenges, including corruption, inefficiency, and lack of responsiveness. Accountability, in the context of public administration, refers to the obligation of public officials to answer for their actions and decisions to stakeholders, including citizens, institutions, and regulatory bodies. It involves mechanisms that ensure the responsible use of power, adherence to legal and ethical standards, and alignment of actions with public interest.